The effect of glycerol to enzyme ratio in enzymatic glycerolysis - Yeoh, Chiou Moi; Choong, Thomas Shean Yaw; Yunus, Robiah; Abdullah, Luqman Chuah; Wai, Lin Siew (2008)
Diacylglycerol is naturally present in oils and fats. It is considered a valuable dietary food product. Recent studies on nutritional properties and dietary effects showed that 1,3-diacylglycerol in contrast to triacylglycerol, is capable of reducing serum triacylglycerol concentration to result in a decrease of both body weight and visceral fat mass. Consequently, an oil with high DAG has drawn attention as a useful oil for the prevention of obesity and other lifestyle-related diseases. The objective is to study the effect of the glycerol to enzyme ratio in enzymatic glycerolysis.